Implementation of evidence based guidelines for paediatric asthma management in a teaching hospital. Issue 7 (21st June 2004) - Massie, J; Efron, D; Cerritelli, B; South, M; Powell, C; Haby, M M; Gilbert, E; Vidmar, S; Carlin, J; Robertson, C F
Abstract : Aims: To evaluate a systematic approach to the development and implementation of evidence based asthma management guidelines. Methods: Comparative study of children (2–18 years) with acute asthma; a control cohort (cohort 1) was recruited before implementation of the guidelines and two cohorts were recruited after implementation (cohorts 2 and 3). Results: There was no difference in the proportion of patients who reattended in the six months following initial presentation for cohort 1 (21.5%), cohort 2 (27.8%), or cohort 3 (25.4%) and no difference in readmission rates (11.4%, 11.3%, 11.0% respectively). There was no difference in measures of asthma morbidity between the cohorts at 3 and 6 months across three domains: interval symptoms, exercise limitation, and bronchodilator use. Of those who did not have a management plan before presentation, one was provided to 46.9% of cohort 1, 74.8% of cohort 2, and 81.1% of cohort 3. There was no difference comparing cohort 2 or cohort 3 with cohort 1 regarding quality of life for either the subjects or their parents. Conclusions: Implementation of our evidence based guidelines was associated with the improved provision of asthma management plans, but there was no effect on reattendance or readmission to hospital, asthma morbidity, or quality of life. Future efforts to improve asthma management should target specific components of asthma care.